Dominasi Gong Kebyar dan Transformasi Musik Tradisional Sasak Dalam Perspektif Akulturasi dan Keaslian Budaya - Ketut Suparta (Jurnal Penelitian Agama Hindu, 2026)
The development of traditional music on the island of Lombok reflects dynamic cultural interactions between the Sasak and Balinese communities that have taken place since the migration of Balinese people to Lombok in the 18th century. One of the most notable influences is the incorporation of musical elements from Balinese Gong Kebyar into Sasak traditional music practices, particularly in Gendang Beleq performances and other traditional art forms. This study aims to analyze how the aesthetic dominance of Gong Kebyar has influenced the development of Sasak traditional music and to understand the forms of musical transformation that occur within the context of cultural acculturation and their implications for local musical identity. The research uses a descriptive qualitative approach with a case study design conducted in Mataram City, West Lombok Regency, and Central Lombok Regency. Data were collected through in-depth interviews with traditional artists, leaders of art studios, customary leaders, and community members who appreciate traditional arts, supported by performance observations and documentation studies. The data were analyzed using a thematic approach to identify patterns of musical dominance, transformations in compositional structure, and shifts in cultural meaning among art practitioners. The results show that the influence of Gong Kebyar appears not only in musical aspects such as rhythmic patterns, dynamics, and compositional structure, but also in performance aesthetics and as a symbol of prestige within the local arts community. The integration of kekebyaran elements has produced hybrid musical expressions that combine Sasak and Balinese traditions. However, this phenomenon also raises debates about the boundary between artistic innovation and the preservation of local cultural identity. Therefore, strengthening documentation, promoting locally based arts education, and expanding ethnomusicological studies are important steps to ensure the sustainability of Sasak traditional music amid ongoing cultural change.